GE_GERICHTE A/4280/2005 vom 28. Januar 2008 - GE Cour de justice (2008)
ASSUJETTISSEMENT(IMPÔT); CALCUL DE L'IMPÔT; IMPÔT SUR LA FORTUNE ET LE CAPITAL ; EXONÉRATION FISCALE | LIPP-III.2. leta; LIPP-I.3. al1. letc; LIPP-I.6; LGL.24A;